Political history and demographic growth and their impact on the urban development of the city of Algiers - mouchmouche, mohamed (Journal of Social Sciences and Humanities, 2025)
The city of Algiers has been influenced by all the historical events in North Africa, from the ancient to the modern, where it has experienced urban development and a major polarization of human, nomadic and urban groups, and even though Islamic era, the tribe of BeniMzaghna was long inhabited. The city experienced an urban expansion that lasted only until the modern era, when its Ottoman rulers added many architectural structures, including religious, military and civil, which encouraged the inhabitants to live. to install and upon arrival of groups. Mortal One of the greatest known migrations of the city of Algeria is that of the Andalusia's, where the city has benefited from the accumulation of Andalusia civilizations in all fields. Many European prisoners, especially those who converted to Islam, were merged with the residents of the city. This human diversity has been positive for the city, both scientifically and architecturally.